An improved reversible data hiding scheme based on pixel permutation. (2019) - Wang, Jilin; Sun, Xiao; Feng, Xiaoqing
Low payload capacity is a flaw in pixel exchange-based reversible data hiding schemes. In order to improve it, this paper proposes a triangular pixel pair structure, which requires fewer pixels than a traditional 2 × 2 pixel block. At the same time, the corresponding embedding conditions are also proposed to screen out those pixel pairs that may reduce image visual quality seriously after data embedding. Embeddable pixel pair is binarised by its feature. And, Huffman coding method is used to create free space for secret data while ensuring reversibility. Eventually, data is embedded into a cover image by switching embeddable pixel pair features. The experimental results show that the greyscale histogram of the cover image is never modified by the proposed scheme. Consequently, secret data cannot be detected by the statistical steganalysis based on the greyscale histogram. Both payload capacity and imperceptibility get enhanced obviously, and PSNR is at the same level as the schemes that do not provide robustness of the greyscale histogram.